Cortisol and behavioral reaction of low and high sensation seekers differ in responding to a sport-specific stressor - Frenkel, M. O.; Heck, R.-B.; Plessner, H. (Anxiety, Stress and Coping, 2018)
Background/objectives: Sensation seeking is closely related to practicing high-risk sports. This domain offers individuals an opportunity to achieve an increased level of arousal. Moreover, stress reactivity implies interindividual differences in the capacity to respond to a stressor. The purpose of this study was to examine whether high sensation seekers (HSS) compared to low sensation seekers (LSS) experience lower levels of stress on a physiological and psychological basis. Stress was induced in a sport-specific experimental paradigm with a climbing task through a jump into the rope.